THE INFLUENCE OF COMPANY SIZE AND FINANCIAL PERFORMANCE TOWARDS INCOME SMOOTHING - Simon Andreas; Hanna Wijaya (Magister Manajemen Institut Bisnis Nusantara, 2019)
The main objective in this research is to test whether Company Size, Return on Assets, and Earnings per Share influence the practice of Income Smoothing. The data in this research is collected from 86 companies listed in manufacturing industry in Indonesia Stock Exchange. The period of the data collected is 3 years from 2013 – 2016. The research model used in this research is multiple regression where the classical assumption tests are conducted prior to find the result of the model by using SPSS 22. Quantitative approach is used in this research to test the raised hypotheses and solve the issues. In conclusion, the results of this research show that variable SIZE does have positive significant influence on Income Smoothing and variable ROA & EPS do not have significant influence on Income Smoothing.